2022
DOI: 10.1037/ppm0000428
|View full text |Cite
|
Sign up to set email alerts
|

Further tests of the media violence–aggression link: Replication and extension of the 7 Nations Project with multiple Latinx samples.

Abstract: Numerous studies from various countries and cultural backgrounds have found a link between media violence consumption and aggressive behaviors and cognition. However, some failures to replicate these findings potentially suggest that some Latinx cultures may be relatively invulnerable to such harmful effects. To investigate this, media violence exposure and aggression data were collected from samples of predominantly Latinx communities in Brazil, Mexico, and Southwest Texas U.S., as well as from a Canadian sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Superhero media exposure positively correlated with all aggression dimensions, specially physical aggression and aggressive emotions. This information is in line with previous research using GAM, where consuming violent content influences an increase in trait aggression (Anderson, Suzuki, et al, 2017;Miles-Novelo et al, 2022): in general, continuous experiences of a situation (e.g., consuming superhero media) can lead to changes in the individual, which with time become stable (Anderson & Bushman, 2018). Superhero media can, for example, strengthen beliefs that justify violence, considering that these characters often use it to achieve their goals and that acts of violence are the most common negative theme in these works (Bauer et al, 2016;Santos et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Superhero media exposure positively correlated with all aggression dimensions, specially physical aggression and aggressive emotions. This information is in line with previous research using GAM, where consuming violent content influences an increase in trait aggression (Anderson, Suzuki, et al, 2017;Miles-Novelo et al, 2022): in general, continuous experiences of a situation (e.g., consuming superhero media) can lead to changes in the individual, which with time become stable (Anderson & Bushman, 2018). Superhero media can, for example, strengthen beliefs that justify violence, considering that these characters often use it to achieve their goals and that acts of violence are the most common negative theme in these works (Bauer et al, 2016;Santos et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Studies using GAM have consistently demonstrated that violent media (that depicts any form of aggression) is one of the risk factors for aggressive behavior, both directly after exposure (e.g., Bushman & Anderson, 2002; Santos et al, 2022) and increasing trait aggression (e.g., Anderson, Bushman, et al, 2017; Miles‐Novelo et al, 2022). However, when the focus is superhero media, mixed results are found.…”
Section: Introductionmentioning
confidence: 99%
“…The main theoretical contribution of this systematic review is for investigations regarding media impacts on behavior and other psychosocial processes (e.g., General Aggression Model, General Learning Model): when we use a stimulus in an experiment or ask a participant about their consumption of certain types of media (e.g., violent), we assume that the effects of these media are unidirectional. Watching or playing violent entertainment media indeed does have impacts on this specific behavior (e.g., Anderson et al, 2017;Miles-Novelo et al, 2022).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Studies have shown that under the stress of the pandemic, the hostility and aggression of the public will increase ( Hammett et al, 2022 ; Wei et al, 2022 ). The general aggression model (GAM) also suggests that situational changes and individual cognitive factors will trigger aggressive behaviors by changing their internal states such as emotions and moods ( Abreu et al, 2021 ; Miles-Novelo et al, 2022 ). At the same time, the pandemic has brought people a sense of social adversity Zhang et al 2017 that represents the individual’s perceptual response to experiencing continuous or recurring negative social events ( Monahan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a positive mood always have a preference for pleasant experiences, explanations and emotional information, and can recall more pleasant materials from memory, while individuals with a negative mood do the opposite ( Niedenthal and Setterlund, 1994 ). According to the theory of Berkowitz (2003) and Miles-Novelo et al (2022) , the spread of negative mood through association networks is likely to stimulate individual aggressiveness.…”
Section: Introductionmentioning
confidence: 99%